Sweet Sweetback’s Baadasssss Song de Melvin Van Peebles (1971) : exégèse d’un film militant - Delphine Letort (Revue LISA)
Sweet Sweetback’s Baadasssss Song represented a turning point in filmmaking when it was released in 1971. This article focuses on the interplay of the political and the aesthetic in a film that was conceived as a means of furthering change in the representation of African Americans. Not only did it support the emergence of black cinema by opening up filmmaking to black crews, but it also broached taboo subjects while depicting black sexuality (miscegenation) and police brutality. Melvin Van Peebles proposed a new heroic figure through the character of Sweetback, whose hypersexuality was to become a mercantile asset in Hollywood blaxploitation films. Nevertheless, the narrative’s reliance on a stereotypical Sweetback undermined its political message.